2014
DOI: 10.2337/db14-0879
|View full text |Cite
|
Sign up to set email alerts
|

Glycated Albumin With Loss of Fatty Acid Binding Capacity Contributes to Enhanced Arachidonate Oxygenation and Platelet Hyperactivity: Relevance in Patients With Type 2 Diabetes

Abstract: High plasma concentrations of nonesterified fatty acids (NEFAs), transported bound to serum albumin, are associated with type 2 diabetes (T2D). The effects of albumin on platelet function were investigated in vitro. Modifications of albumin, such as those due to glycoxidation, were found in patients with T2D, and the consequences of these modifications on biological mechanisms related to NEFA handling were investigated. Mass spectrometry profiles of albumin from patients with T2D differed from those from healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
29
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 63 publications
2
29
0
2
Order By: Relevance
“…Previous studies reported that oxidative stress and glycation resulted in conformational changes in albumin structure and function in vitro [21,49,50], and recently in vivo by the altered fatty acid binding capacity displayed by albumin isolated from diabetic patients [51]. The present study provides novel insights into redox imbalance in the liver of diabetic/obese mice and highlights.…”
Section: Discussionsupporting
confidence: 51%
“…Previous studies reported that oxidative stress and glycation resulted in conformational changes in albumin structure and function in vitro [21,49,50], and recently in vivo by the altered fatty acid binding capacity displayed by albumin isolated from diabetic patients [51]. The present study provides novel insights into redox imbalance in the liver of diabetic/obese mice and highlights.…”
Section: Discussionsupporting
confidence: 51%
“…Thus, glycation of certain HSA residues appears to be directly linked to its capacity for transporting FFAs. Indeed, Blache et al demonstrated that albumin loses approximately 30% of its FFA binding capacity when incubated with a mixture of glucose and methylglyoxal, yielding Amadori products and advanced glycation end products (AGEs), respectively. Thus, higher degrees of glycation may promote higher levels of unbound circulating FFA, increasing the risk of thrombosis, platelet activation, sudden death, stroke and coronary artery disease .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, glycation of certain HSA residues appears to be directly linked to its capacity for transporting FFAs. Indeed, Blache et al 56 demonstrated that albumin loses approximately 30% of its FFA binding capacity when incubated with a mixture of glucose and methylglyoxal, yielding Amadori products and advanced glycation end products (AGEs), respectively.…”
Section: Discussionmentioning
confidence: 99%
“…It is in the context of these previous observations that Blache et al (17) have now investigated the paradigm that the glycation or glycoxidation of albumin is relevant to NEFA-related pathophysiology as such modifications of albumin would potentially result in an impaired binding to NEFAs and an increase in unbound NEFAs and thus to platelet hyperactivity. The authors have shown that glycation of albumin induced in vitro with glucose or methylglyoxal, an advanced glycation end product, leads to a reduction in the binding of NEFA to albumin; these changes were similar to those observed in albumin prepared from patients with diabetes.…”
mentioning
confidence: 99%